Characterizing the Free‐Energy Landscape of MDM2 Protein–Ligand Interactions by Steered Molecular Dynamics Simulations. (15th June 2015) - Hu, Guodong; Xu, Shicai; Wang, Jihua
Abstract : Inhibition of p53–MDM2 interaction by small molecules is considered to be a promising approach to re‐activate wild‐type p53 for tumor suppression. Several inhibitors of the MDM2–p53 interaction were designed and studied by the experimental methods and the molecular dynamics simulation. However, the unbinding mechanism was still unclear. The steered molecular dynamics simulations combined with Brownian dynamics fluctuation–dissipation theorem were employed to obtain the free‐energy landscape of unbinding between MDM2 and their four ligands. It was shown that compounds4 and8 dissociate faster than compounds5 and7 . The absolute binding free energies for these four ligands are in close agreement with experimental results. The open movement of helix II and helix IV in the MDM2 protein‐binding pocket upon unbinding is also consistent with experimental MDM2‐unbound conformation. We further found that different binding mechanisms among different ligands are associated with H‐bond with Lys51 and Glu25. These mechanistic results may be useful for improving ligand design. Abstract : Four ligands were dragged out from their MDM2 protein‐binding pocket. The differences in free energies calculated by BD‐FDT are in agreement with the experimental data. We further found that different binding mechanisms among different ligands are associated with H‐bond with Lys51 and Glu25.